(untitled) (Bioscience Journal, 2022)
The study aimed to analyze the quality of life, oral health impact on daily activities and its association with adherence to dental treatment, and other factors, among vulnerable adolescents. It is a longitudinal analytical study performed with 15- to 19-year-old adolescents in the city of Piracicaba, São Paulo, from 2014 to 2015. The sample consisted of 476 adolescents referred for the treatment of caries and/or periodontal disease in family health units (initial phase). After 18 months, 325 individuals were assessed to investigate the dental treatment provided (final phase). The response variables considered in the final phase were the Quality of Life (WHOQOL-bref) and the Oral Impacts on Daily Performances (OIDP) questionnaires. The independent variables analyzed were sex, age, treatment adherence, and family cohesion and adaptability. A multiple regression model was used. The data on the physical (p<0.0001), social (p=0.0003), environmental (p<0.0001), and psychological (p<0.0001) domains of the WHOQOL collected in the initial phase had a positive relationship with the same domains assessed in the final phase. The WHOQOL data of the initial phase were associated with the WHOQOL data of the final phase (p=0.0341). The OIDP data of the initial phase were associated with the OIDP data of the final phase (p<0.0001). The OIDP of volunteers who did not adhere to dental treatment showed a higher impact (p=0.0234). The quality of life and impacts on daily performances of adolescents improved between the evaluation periods.